Implementasi Metode Group Work dalam Mengasah Bakat Bermusik Anak-anak Panti Asuhan Simpang Tiga Medan - Todo Anugrah Simbolon; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
A child needs a parent figure in the stage of growth and development. Parents play an important role in caring for and educating children so that later the child can grow into someone who can make their parents proud. But what if a child doesn't have parental figures in his life? What will be the future for the child if the parents don't want to guide their child, or if the parents are gone, can the child still enjoy his future? Orphanage is a solution to this problem. Orphanage is a place to live for children who are less fortunate due to being abandoned by their parents for various reasons and backgrounds. Every child who is in an orphanage is given services according to what they should get in the family. The needs of food, boards, and clothing, all as much as possible is provided according to needs. Different backgrounds also become a challenge for caregivers. Understanding each character and potential of each child needs to be done, so that children can develop according to their abilities and talents. Thus they will be the same as other children who live with their parents.